Pengaruh Lingkungan Kerja Fisik dan Non Fisik Terhadap Kinerja Karyawan di Grand Lagoi Hotel Bintan (International Forum of Researchers and Lecturers, 2024)
The finding of phenomena related to the physical and non-physical work environment on employee performance at the Grand Lagoi Hotel Bintan is the reason for conducting this research. This research is aimed at investigating how the physical and non-physical work environment is influenced by employee performance. By using a survey methodology based on a quantitative causal associative framework, this research seeks to explain the causal dynamics that occur. Then, the population used was employees at the Grand Lagoi Hotel Bintan. A total of 77 respondents participated in this study, selected through saturated sampling techniques to ensure comprehensive representation. To assess the validity and reliability of the questionnaire—the main instrument for data collection using a Likert scale. For data analysis, we used the SPSS 20.00 application, ensuring robust and accurate processing of the findings. The resulting findings indicate that the results of the Physical and Non-Physical Work Environment have a significant influence on Employee Performance at Grand Lagoi Hotel Bintan.